Understanding rural poverty and investment in agriculture: an assessment of integrated quantitative and qualitative research in Western Kenya - Place, Frank; Adato, Michelle; Hebinck, Paul (Elsevier, 2007)
This article addresses the methodological complexities inherent in researching poverty, examining how to differentiate the poor from other social groups, and how to assess the relationships between poverty and technology adoption and impact. The use of specific types of quantitative and qualitative methods, the degree to which their integration was achieved, and the benefits of integration are analyzed. Qualitative and quantitative methods are both necessary for understanding the relationship between poverty and technology adoption, but significant interactions between the scientists at all stages of the research is required for the benefits to be fully achieved.